2020
DOI: 10.36740/wlek202002125
|View full text |Cite
|
Sign up to set email alerts
|

Checking of the methodical system efficiency of fitness technologies application in students’ physical education

Abstract: The aim is to carry out a comparative analysis of the effectiveness of the traditional system of physical education of students in higher pedagogical education establishments and authors’methodical system of fitness technologies application. Materials and methods: Two hundred thirty two students of Zhytomyr Ivan Franko State University (n=232; 88 males and 144 females) aged from 18 to 20 years old took part in the research. Two experimental groups (EG, 47 males and 71 females) and two control groups (CG, 41 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 21 publications
5
30
0
2
Order By: Relevance
“…The analysis of the dynamics of physical health showed that there was a tendency for health improvement in both groups. However, the level of health improved by 1/08 points in the CG (р<0.01), and by 5.7 points in the EG (р<0.001) that confirms the results of many studies [5,13,17] on the positive impact of sports on improving students' health. The assessment of the physical health level of students in accordance with Table I designated that the level of health corresponded to a low level in the CG at all stages of the study, and in EG, it corresponded to a low level in the 1st term, below the middle in the 2nd and 3rd terms, and the middle in the 4th term.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The analysis of the dynamics of physical health showed that there was a tendency for health improvement in both groups. However, the level of health improved by 1/08 points in the CG (р<0.01), and by 5.7 points in the EG (р<0.001) that confirms the results of many studies [5,13,17] on the positive impact of sports on improving students' health. The assessment of the physical health level of students in accordance with Table I designated that the level of health corresponded to a low level in the CG at all stages of the study, and in EG, it corresponded to a low level in the 1st term, below the middle in the 2nd and 3rd terms, and the middle in the 4th term.…”
Section: Resultssupporting
confidence: 85%
“…The scientists [15,16] point out that some factors of life and socially hygienic living conditions, as well as studying at HEI do not provide optimal health for students. As a result of students testing, scientists [17] defined the initial level of physical fitness of the first-year students, among whom 18 % showed a low level; 49 % -lower than the middle (unsatisfactory grade); 20 % -the middle level (satisfactory grade); 13 % -above the middle (good grade). No students with a high level of physical fitness were found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…those that influence several human signaling systems. Interactive technologies include modern video technologies with the use of computer programswebsites, video films, activating the need for a healthy lifestyle, the desire for beauty, harmony, preservation of life [30]. In addition, it is necessary to strengthen educational work and advocacy of the importance of a healthy lifestyle among young students, to create clubs for interesting leisure, to expand sports and cultural events, and introduce incentives for a healthy lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in researches of scientists fitness technologies studied in methodological and organizational aspects. Scientists agree that fitness technology improves the quality of physical education classes in higher education establishments, meet the needs of students in improving health, contribute to the development of a positive and active attitude to a healthy lifestyle, the formation of motor skills and abilities [2,5,12,16,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]33].…”
Section: Introductionmentioning
confidence: 99%